2008
DOI: 10.1007/s12576-008-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of end-tidal CO2 pressure during exercise in patients with left ventricular dysfunction

Abstract: We compared the prognostic power of end-tidal CO 2 pressure (PETCO 2 ) during exercise, an index of arterial CO 2 pressure, with those of established respiratory gas indexes during exercise testing in patients with left ventricular dysfunction. Seventy-eight consecutive patients with a left ventricular ejection fraction (LVEF) B40% were enrolled in the study. All the patients performed a symptom-limited incremental exercise test with respiratory gas measurements. PETCO 2 at peak exercise, peak O 2 uptake ( _ V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…15 Very recently, it has been shown that low PETCO2 measured during exercise predicts poor outcome in patients with LV dysfunction. 16 These findings strongly suggest that a lower PETCO2 during exercise caused by the V/Q mismatch, and additionally by a reduced PaCO2 such as at peak exercise when the subject hyperventilates in response to the lactic acidosis, is strongly related to insufficient cardiac reserve. In contrast, the clinical significance of PETO2 during exercise has rarely been reported in cardiac patients.…”
Section: Discussionmentioning
confidence: 87%
“…15 Very recently, it has been shown that low PETCO2 measured during exercise predicts poor outcome in patients with LV dysfunction. 16 These findings strongly suggest that a lower PETCO2 during exercise caused by the V/Q mismatch, and additionally by a reduced PaCO2 such as at peak exercise when the subject hyperventilates in response to the lactic acidosis, is strongly related to insufficient cardiac reserve. In contrast, the clinical significance of PETO2 during exercise has rarely been reported in cardiac patients.…”
Section: Discussionmentioning
confidence: 87%
“…Кроме того, у 31% испытуемых было зарегистрировано отсутствие прироста данного показателя при КПНТ. Полученные данные соотносятся с результатами других исследований [7,10]. Глубокое угнетение сердечной деятельности у пациентов-кандидатов на ТС обуславливает отсутствие в данной группе адекватного прироста сердечного выброса при выполнении нагрузки, что приводит к снижению эффективности доставки кислорода к работающим мышцам, более раннему наступлению анаэробного порога, и соответственно, повышению нагрузки на респираторное Несмотря на доказанную прогностическую значимость VO 2 peak и VE/VCO 2 slope в стратификации риска не только при сердечно-сосудистых, но и при многих других нозологиях, изучение ассоциаций параметров легочного газообмена, состояния резервных возможностей организма с исходом развития заболеваний и эффективностью лечения остается актуальным [5,15,16].…”
Section: Discussionunclassified
“…PetCO 2 отражает концентрацию углекислого газа в конце выдоха, измерение его неинвазивно и является неотъемлемой частью КПНТ. Немногочисленные исследования показали связь уровня PetCO 2 с тяжестью ХСН [7][8][9]. В одном из исследований даже сообщалось, что PetCO 2 является более сильным предиктором неблагоприятного исхода у пациентов с ХСН, чем VO 2 peak [10].…”
Section: Introductionunclassified
“…Regardless of the exact mechanism, abnormally low values at the LT have been found useful for the diagnosis of pulmonary vascular diseases in patients with unexplained dyspnea [111]. There is now established evidence that P ET CO 2 at rest [112114], LT [115], and peak exercise [116] are valuable for prognosis estimation and disease severity assessment in CHF [219, 220]. Low P ET CO 2 values have also been found in PAH (see also later) [97, 111, 117, 118].…”
Section: Ventilatory Responsesmentioning
confidence: 99%
“…In fact, Yasunobu and co-workers suggested that observation of an unusually low P ET CO 2 at the LT (<30 mmHg or, in particular, <20 mmHg) in a patient with exertional dyspnea of unknown cause without evidence of acute hyperventilation (ie, normal R) should prompt the hypothesis of pulmonary vasculopathy [111]. P ET CO 2 response profile is also informative as failure to increase below the LT or progressive decreases from the start of exercise are associated with worsening clinical and hemodynamic impairment (Figures 9(b) to 9(e)) [111] and are rarely found in CHF [112116]. Based on (2), it might be expected that if P ET CO 2 changed parallel to P A CO 2 , a hyperbolic relationship between   trueV˙E/trueV˙COnormal2 and P ET CO 2 at the LT would result.…”
Section: Ventilatory Responsesmentioning
confidence: 99%